Consolidated Management Report. Innovations in Managerial Reporting Practices - Bezverkhiy, K. V.; Panteleev, V. P. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
Consolidated report on management is a new phenomenon in the Ukrainian reporting practices due to the adoption of amendments to the Law of Ukraine “On Accounting and Financial Reporting in Ukraine”. The consolidated management report is intended to bring the information provision of a group of companies up to a radically new level. An extensive review of the content of the consolidated management report is made, to show that it represents an important component in the financial reporting of a group of companies; it should contain true and fair overview of the performance of a group of companies, conforming to the scopes and complexity of their business; this information should not be confined to financial aspects of business, but should encompass analysis of ecological and social issues of the business, which users of the reporting need to comprehend business performance, trends and prospects of the company group. A comparative review of legal acts of EU and Ukraine on consolidated report is given. The procedure for presenting non-financial information in the report by the EU practice is highlighted. The specifics of consolidated financial report- ing for micro-, small and medium companies are shown. Results of the study can contribute to solutions of problems related with harmonization of reporting in Ukraine with the EU standards. There are recommended for use at all the groups of companies in Ukraine, in various economic sectors, which are expected to make consolidated management repor.